FORMING MODELING OF A SINGLE-PRODUCT PRODUCTION PROGRAM OF AN ENTERPRISE AT THE EXPENCE OF OWN MEANS - N. A. Sokolitsyna (Дискурс)
Economic-mathematical models of forming enterprise production program with single-product taking into account free store capacity, average labor of product, market demand and other basic resources realized at the expense of own means were elaborated, which differ in forming of set tasks solutions by means of pessimistic and optimistic variants of calculation in terms of the objective function - profit maximum.